Lithium supplementing material, preparation method and application thereof
Patent Information
- Application Number
- CN202611379449.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]针对现有技术中无法同时兼顾高补锂容量、优异脱锂动力学与良好空气储存稳定性的缺陷,本发明提出一种补锂材料及其制备方法和应用
1、本发明采用NbSe2包覆层结构致密且具备疏水特性,可在Li5FeO4颗粒表面形成物理阻隔屏障,有效阻挡空气中H2O、CO2向基体内部渗透,抑制Li5FeO4表面活性锂生成LiOH、Li2CO3等残碱杂质,在湿度环境中暴露24 h后仍可维持较高容量保持率,大幅改善纯Li5FeO4易受潮劣化的缺陷。
Smart Images

Figure CN122907764A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery materials technology, and in particular to a lithium supplementation material, its preparation method, and its application. Background Technology
[0002] During the first charge and discharge cycle of a lithium-ion battery, the electrolyte undergoes reduction and decomposition on the electrode surface, generating a solid electrolyte interphase (SEI) film. This process irreversibly consumes a large amount of free lithium in the electrolyte, resulting in internal lithium loss and directly reducing the battery's initial coulombic efficiency, actual reversible capacity, and cycle life. To compensate for irreversible lithium loss and improve cell energy density, the industry commonly employs pre-lithiation technology, introducing lithium-rich materials into the electrode system to replenish active lithium. Li5FeO4 is a promising iron-based lithium-rich material with high theoretical delithiation capacity, low raw material cost, environmental friendliness, and a delithiation potential compatible with mainstream lithium-ion battery systems. However, pure-phase Li5FeO4 powder has defects that limit its practical application.
[0003] Li5FeO4 exhibits significant intrinsic semiconductor characteristics, but its particles have high electronic conduction resistance, slow delithiation kinetics, and severe polarization during charge and discharge. Under high capacity conditions, the actual release capacity for lithium replenishment decreases significantly. The surface of Li5FeO4 is rich in highly active free lithium sites, which readily react with moisture and CO2 when exposed to air to generate residual alkalis such as LiOH and Li2CO3. This not only causes irreversible capacity loss but also makes electrode slurry coating difficult.
[0004] Therefore, there is an urgent need to develop a new type of modified lithium replenishment material that can simultaneously solve the dual problems of poor conductivity and easy deterioration due to moisture in Li5FeO4. Summary of the Invention
[0005] To address the shortcomings of existing technologies that cannot simultaneously achieve high lithium replenishment capacity, excellent delithiation kinetics, and good air storage stability, this invention proposes a lithium replenishment material, its preparation method, and its applications.
[0006] The present invention provides a lithium supplementation material, comprising a lithium ferrite matrix and a coating layer covering the surface of the lithium ferrite matrix; The coating layer includes a coating layer material, and the coating layer material is niobium diselenide; The lithium ferrite matrix is Li5FeO4.
[0007] This invention selects niobium diselenide (NbSe2) as the surface coating material. NbSe2 is a typical transition metal dichalcogenide (TMD) with a graphite-like layered structure. The layers are bonded by weak van der Waals forces, allowing for rapid lithium-ion insertion and transport. More importantly, NbSe2 exhibits metallic conductivity at room temperature, with excellent bulk conductivity, and its layered structure facilitates the formation of dense nanolayers. Using NbSe2 as the coating layer results in a dense structure and excellent conductivity, which can significantly improve the air stability and conductivity of Li5FeO4.
[0008] In some embodiments, the coating amount of niobium diselenide is 0.5 wt% to 10 wt% based on the total mass of the lithium supplementation material.
[0009] In some embodiments, the coating amount of niobium diselenide is 1 wt% to 5 wt% based on the total mass of the lithium supplementation material.
[0010] This invention balances functional modification and the proportion of active components in the matrix by precisely controlling the amount of coating layer: if the coating amount is too low, a complete and continuous barrier and conductive layer cannot be formed, resulting in insufficient modification effect; if the coating amount is too high, the non-lithiating NbSe2 will excessively dilute the Li5FeO4 matrix, causing a significant decrease in the lithium replenishment capacity per unit mass. Within the optimal range, the NbSe2 coating layer can simultaneously achieve the dual functions of a highly conductive pathway and a dense hydrophobic barrier, simultaneously optimizing the material's delithiation kinetics and air storage stability without sacrificing lithium replenishment capacity.
[0011] This invention also provides a method for preparing the aforementioned lithium-supplementing material, comprising the following steps: (1) Disperse Li5FeO4 in a solvent to obtain a suspension; (2) Disperse the niobium source and selenium source in a solvent, add a reducing agent, and stir to obtain a precursor solution; (3) Under an inert atmosphere, the precursor solution is added dropwise to the suspension, stirred and mixed, then transferred to a high-pressure reactor and reacted at 180~220℃ for 12~24 hours. After washing and drying, the lithium supplement material is obtained.
[0012] In some embodiments, the solvent in step (1) or (2) is anhydrous ethanol or N-methylpyrrolidone; by using anhydrous ethanol or N-methylpyrrolidone as an anhydrous inert organic solvent, the hydrolysis side reaction between Li5FeO4 and water can be completely avoided.
[0013] In some embodiments, the niobium source in step (2) includes niobium pentachloride or niobium ethanol; The selenium source includes selenium powder; The reducing agent is hydrazine hydrate or sodium borohydride.
[0014] In some embodiments, the molar ratio of niobium source to selenium source in step (2) is 1:(2~3). Selenium powder has a low melting point (about 217°C) and is easily volatile. Excessive selenium source ensures the generation of NbSe2. At the same time, maintaining a high concentration of active selenium ions in the solution is beneficial for rapid nucleation and uniform coating, and avoids incomplete coating growth due to instantaneous depletion of selenium source.
[0015] The present invention also provides the application of the lithium-filling material in the preparation of lithium-ion batteries.
[0016] The present invention also provides a positive electrode sheet containing the aforementioned lithium-supplementing material.
[0017] The present invention also provides a lithium-ion battery, including the aforementioned positive electrode sheet.
[0018] In summary, compared with the prior art, the present invention achieves the following technical effects: 1. The present invention employs a dense NbSe2 coating layer with hydrophobic properties, which can form a physical barrier on the surface of Li5FeO4 particles, effectively preventing H2O and CO2 in the air from penetrating into the matrix, inhibiting the formation of residual alkaline impurities such as LiOH and Li2CO3 on the surface of Li5FeO4 active lithium, and maintaining a high capacity retention rate even after exposure to a humid environment for 24 hours, thus significantly improving the defect of pure Li5FeO4 being easily degraded by moisture.
[0019] 2. NbSe2 itself has metallic high conductivity properties, which can build a continuous conductive network between Li5FeO4 particles, solving the problem of increased interface impedance caused by traditional insulating oxide coatings such as Al2O3; at the same time, the unique layered crystal structure of NbSe2 can provide a fast lithium-ion transport channel, simultaneously reducing the electronic transport impedance and lithium-ion diffusion resistance of the system, reducing delithiation polarization, and improving the actual release lithium replenishment capacity and rate performance of the material. Attached Figure Description
[0020] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 This is a SEM image of NbSe2-coated Li5FeO4 prepared in Example 1 of this invention.
[0022] Figure 2 The image shows the XRD pattern of NbSe2-coated Li5FeO4 prepared in Example 1 of this invention.
[0023] Figure 3 The charge-discharge curves of NbSe2-coated Li5FeO4 prepared in Example 1 of this invention are shown. Detailed Implementation
[0024] To enable those skilled in the art to better understand the present invention, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.
[0025] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0026] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, all materials and reagents used are commercially available.
[0027] Example 1 5 g of Li5FeO4 powder (purchased from Shenzhen Yanyi New Materials Co., Ltd.) was weighed and added to 100 mL of anhydrous ethanol. The mixture was ultrasonically dispersed for 1 hour to obtain suspension A. 0.10 g of NbCl5 and 0.075 g of Se powder were weighed and dispersed in 30 mL of anhydrous ethanol. 0.8 mL of hydrazine hydrate was added dropwise as a reducing agent, and the mixture was stirred for 30 minutes to form suspension B. In an argon-filled glove box, suspension B was added dropwise to suspension A at a rate of 10 mL / min. The mixture was then transferred to a polytetrafluoroethylene-lined high-pressure reactor, sealed, and maintained at 200°C for 18 hours. The product was washed with ethanol and deionized water, and then vacuum-dried at 80°C for 12 hours to obtain approximately 2.5 wt% NbSe2-coated Li5FeO4.
[0028] Example 2 5 g of Li5FeO4 and 0.125 g of NbSe2 powder (purchased from the Maclean's website) were weighed and placed in a zirconia ball mill jar in an argon-filled glove box. The ball-to-powder mass ratio was 20:1. The mixture was ball-milled in a planetary ball mill at 300 rpm for 5 hours. After ball milling, the mixture was transferred to a tube furnace and heat-treated at 250°C for 2 hours in an argon atmosphere to obtain Li5FeO4 material coated with NbSe2 with a coating weight of 2.5 wt%.
[0029] Under the high-energy mechanical shearing force of a planetary ball mill, NbSe2 powder is gradually refined and pressed and spread on the surface of Li5FeO4 particles, so that NbSe2 sheets adhere to the surface of Li5FeO4 particles to form a preliminary coating. Subsequently, it is heat-treated at 250°C for 2 hours in an argon flow to promote the extension and adhesion of NbSe2 sheets on the particle surface, thereby further densifying the preliminary coating layer and making it more firmly bonded to the substrate surface, thus forming NbSe2-coated Li5FeO4 material.
[0030] Example 3 The amounts of niobium source and selenium source were adjusted to 0.02 g NbCl5 and 0.015 g Se powder, respectively, so that the NbSe2 coating amount in the product was 0.5 wt%. The remaining steps were the same as in Example 1.
[0031] Example 4 The amounts of niobium source and selenium source were adjusted to 0.4 g NbCl5 and 0.3 g Se powder, respectively, so that the NbSe2 coating amount in the product was 10 wt%. The remaining steps were the same as in Example 1.
[0032] Example 5 The amount of hydrazine hydrate added was 0.4 mL, and the remaining steps were the same as in Example 1.
[0033] Example 6 Replace 0.8 mL of hydrazine hydrate with 0.05 g of sodium borohydride, and follow the same steps as in Example 1.
[0034] Comparative Example 1 Using an alumina coating strategy, 5.0 g of Li5FeO4 powder was weighed and transferred to a 250 mL three-necked flask. 100 mL of anhydrous ethanol was added, and the mixture was ultrasonically dispersed for 30 minutes with continuous mechanical stirring to form a homogeneous suspension. Based on a target coating amount of 2.5 wt% Al2O3, 0.26 g of aluminum isopropoxide was dissolved in 30 mL of anhydrous ethanol to prepare a precursor solution. This precursor solution was added dropwise to the suspension at a rate of 1–2 mL / min under argon protection and continuous stirring for 1 hour to allow the aluminum isopropoxide to fully adsorb onto the particle surface. Subsequently, a mixed hydrolysis solution consisting of 5 mL of deionized water and 20 mL of anhydrous ethanol (water to aluminum isopropoxide molar ratio approximately 6:1) was slowly added dropwise at a rate of 0.5 mL / min. Stirring was continued at room temperature for 4 hours to complete the hydrolysis and precipitation. After the reaction, the solid was centrifuged, washed three times with anhydrous ethanol, and dried under vacuum at 80 °C for 12 hours. Finally, the dried powder was placed in a tube furnace and dried under an argon atmosphere at 2 °C. The temperature was increased to 300 °C at a rate of °C / min and held for 2 hours to dehydrate the surface hydroxides and convert them into an Al2O3 coating layer. After cooling, Li5FeO4 material with approximately 2.5 wt% Al2O3 coating was obtained.
[0035] Comparative Example 2 Using glucose as a carbon source, 5.0 g of Li5FeO4 powder and 0.5 g of glucose were ball-milled at 300 rpm for 5 h in an inert atmosphere with a ball-to-powder mass ratio of 20:1. The mixture was then heated to 600 °C at 5 °C / min and held for 3 h in an argon atmosphere to obtain 2.5 wt% carbon-coated Li5FeO4.
[0036] Comparative Example 3 Using the solvothermal method of Example 1, the amounts of niobium source and selenium source were adjusted to 0.6 g NbCl5 and 0.45 g Se powder, respectively, so that the NbSe2 coating amount reached 15 wt%.
[0037] Comparative Example 4 Weigh 0.025g of NbSe2 powder and 0.975g of Li5FeO4 and grind and mix them in a mortar.
[0038] Comparative Example 5 No treatment is performed on Li5FeO4.
[0039] Test method: SEM and XRD tests were performed on the sample from Example 1, and the test results are as follows: Figures 1-2 As shown, a dense coating layer of sheet-like NbSe2 is formed on the surface of Li5FeO4, and the XRD of the obtained material shows that the phase purity is good.
[0040] The air stability test conditions were: temperature 25℃, relative humidity 25%, and the battery was assembled and tested after 24 hours of exposure.
[0041] All electrochemical tests were performed using CR2032 coin cells with lithium metal as the negative electrode and a 1 mol / L LiPF6 solution in a 1:1 volume ratio of ethylene carbonate (EC) to dimethyl carbonate (DMC) as the electrolyte. Initial charge-discharge cycles were conducted at 2.0–4.5 V (vs. Li). + Within the / Li voltage range, it is charged at a constant current of 0.05C and discharged at a constant current of 0.1C.
[0042] The results are as follows Figure 3 As shown, the delithiation potential of Li5FeO4 coated with NbSe2 is significantly reduced to 3.25V.
[0043] The electrochemical performance and air stability test results of the Li5FeO4 materials obtained in the examples and comparative examples are shown in Table 1 below: Table 1. Electrochemical performance and air stability test results
[0044] As shown in Table 1, the NbSe2-coated samples of this invention can maintain or even improve lithium replenishment capacity within a reasonable coating amount range. The preparation process has a significant impact on lithium replenishment capacity; the NbSe2-coated samples prepared by the solvothermal method exhibit significantly better capacity performance than samples with the same coating amount prepared by ball milling or direct grinding. Regarding delithiation kinetics, the NbSe2-coated samples of this invention can significantly reduce the delithiation potential and greatly improve delithiation kinetics, with the improvement further enhanced by increasing NbSe2 coating amount. In terms of preparation process, the samples prepared by the solvothermal method have the best kinetic performance; the uniform and dense coating layer is more conducive to constructing continuous conductive channels, reducing electron transport impedance and lithium-ion diffusion resistance, and further reducing delithiation polarization. Regarding air stability, the NbSe2-coated samples of this invention have better air stability, forming a dense hydrophobic physical barrier on the Li5FeO4 surface, significantly inhibiting material deterioration due to moisture, and the air stability further enhances by increasing NbSe2 coating amount. In terms of preparation process, the samples prepared by the solvothermal method have better coating density, better physical barrier effect, and significantly better air stability than the samples prepared by the physical mixing process.
[0045] Compared to the examples, Comparative Example 1, with its alumina coating, significantly increases the interfacial impedance of the particles, hindering electron transport, exacerbating delithiation polarization, raising the delithiation potential, and causing a decrease in lithium replenishment capacity. It only improves moisture resistance but sacrifices material conductivity and delithiation kinetics, resulting in a significantly inferior overall performance compared to the examples. Comparative Example 2 uses glucose pyrolysis carbon to coat modified Li5FeO4. The carbon layer has good conductivity, which can slightly optimize the material's electronic conductivity, alleviate delithiation polarization, and slightly improve lithium replenishment capacity. However, the carbon layer structure is loose and porous, with poor hydrophobic barrier properties, making it difficult to prevent moisture from penetrating into the particles. The improvement in air stability is limited; it only improves conductivity and cannot simultaneously address the two core requirements of conductivity and moisture resistance. In Comparative Example 3, the excess niobium diselenide can construct a complete and continuous conductive network while forming a dense hydrophobic barrier layer. Therefore, the material's delithiation kinetics and air stability reach the best level among all samples. However, the large amount of non-lithiative NbSe2 dilutes the proportion of the Li5FeO4 matrix, directly leading to a significant decrease in the lithium replenishment capacity per unit mass. Over-coating severely damages the material's core lithium replenishment capacity, rendering it unusable for practical applications. Comparative Example 4 only achieves simple powder blending through mechanical grinding, failing to form a continuous and dense coating layer on the surface of Li5FeO4 particles. This makes it difficult to build a stable conductive path, resulting in a weak improvement in delithiation polarization. Furthermore, it cannot form an effective hydrophobic barrier, allowing moisture to easily penetrate the matrix, thus limiting the improvement in air stability. Comparative Example 5 uses a pure Li5FeO4 matrix. The material itself has poor delithiation kinetics and severe delithiation polarization. Simultaneously, the particle surface contains a large number of highly active lithium sites, which readily react with water and carbon dioxide upon exposure to air, generating residual alkali impurities, resulting in severe irreversible capacity loss and extremely poor air stability.
[0046] In summary, the NbSe2 coating of the present invention, with a reasonable coating amount (preferably 1~5 wt%), can simultaneously achieve the following comprehensive advantages: almost no sacrifice or even improvement in the first charge specific capacity, significant improvement in high rate performance, and greatly enhanced air storage stability. Its comprehensive performance is unmatched by traditional carbon coating or oxide coating.
[0047] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A lithium supplementation material, characterized in that, It includes a lithium ferrite matrix and a coating layer covering the surface of the lithium ferrite matrix; The coating layer includes a coating layer material, and the coating layer material is niobium diselenide; The lithium ferrite matrix is Li5FeO4; The coating amount of niobium diselenide is 0.5 wt% to 10 wt%.
2. The lithium replenishment material according to claim 1, characterized in that, The coating amount of niobium diselenide is 1 wt% to 5 wt% based on the total mass of the lithium supplement material.
3. The method for preparing the lithium-supplementing material according to any one of claims 1 to 2, characterized in that, Includes the following steps: (1) Disperse Li5FeO4 in a solvent to obtain a suspension; (2) Disperse the niobium source and selenium source in a solvent, add a reducing agent, and stir to obtain a precursor solution; (3) Under an inert atmosphere, the precursor solution is added dropwise to the suspension, stirred and mixed, then transferred to a high-pressure reactor and reacted at 180~220℃ for 12~24 hours. After washing and drying, the lithium supplement material is obtained. The solvent in step (1) or (2) is anhydrous ethanol or N-methylpyrrolidone; The reducing agent is hydrazine hydrate or sodium borohydride.
4. The method for preparing the lithium-supplementing material according to claim 3, characterized in that, The niobium source in step (2) includes niobium pentachloride or niobium ethanol; The selenium source includes selenium powder.
5. The method for preparing the lithium-supplementing material according to claim 3, characterized in that, The molar ratio of niobium source and selenium source in step (2) is 1:(2~3).
6. The application of the lithium-replenishing material according to any one of claims 1 to 2 in the preparation of lithium-ion batteries.
7. A positive electrode plate, characterized in that, The positive electrode contains the lithium supplementation material as described in any one of claims 1 to 2.
8. A lithium-ion battery, characterized in that, Includes the positive electrode sheet as described in claim 7.